2022
DOI: 10.3389/fbioe.2021.811417
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating CD4+ T Cell Pathways to Prevent Preeclampsia

Abstract: Preeclampsia (PreE) is a placental disorder characterized by hypertension (HTN), proteinuria, and oxidative stress. Individuals with PreE and their children are at an increased risk of serious short- and long-term complications, such as cardiovascular disease, end-organ failure, HTN, neurodevelopmental disorders, and more. Currently, delivery is the only cure for PreE, which remains a leading cause of morbidity and mortality among pregnant individuals and neonates. There is evidence that an imbalance favoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 131 publications
2
12
0
Order By: Relevance
“…Previous studies have demonstrated decreased NK cell and Treg frequency in the peripheral blood and decidua, which may be associated with the pathophysiology of PE 63–70 . We similarly found decreased maternal peripheral NK cells and Tregs in PE cases compared to controls.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have demonstrated decreased NK cell and Treg frequency in the peripheral blood and decidua, which may be associated with the pathophysiology of PE 63–70 . We similarly found decreased maternal peripheral NK cells and Tregs in PE cases compared to controls.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have demonstrated decreased NK cell and Treg frequency in the peripheral blood and decidua, which may be associated with the pathophysiology of PE. [63][64][65][66][67][68][69][70] We similarly found decreased maternal peripheral NK cells and Tregs in PE cases compared to controls. We also found decreased NK cell and Treg frequency with advancing gestational age in controls, similar to prior findings.…”
Section: Principal Findingssupporting
confidence: 59%
“…Recently, evidence from studies has emerged supporting the idea that mesenchymal stem cells might be part of the fetomaternal tolerance environment. CD4+ T cells can regulate antigen‐presenting cell maturation, cytotoxic behavior of NK cells, placental trophoblasts cells, and maternal vascular endothelium, thereby immune‐modulating at the maternal‐fetal interface 134 …”
Section: Maternal Immune Cross Talk: Humoral and Cell‐mediated Immune...mentioning
confidence: 99%
“…In preeclampsia women, the maternal immune response, against the fetus, interferes with trophoblast invasion and angiogenesis, resulting in oxidative stress and a maternal systemic inflammatory response [68]. Immunity imbalance of Th1/Th2 cells, Th17/Treg cells and abnormal regulation of decidual NK cells will lead to the failure of trophoblast invasion and the reduction of placental perfusion, which would generate of reactive oxygen species, and the aggravate of oxidative stress Autoreactive antibodies to the angiotensin receptor AT1 are elevated in preeclamptic mothers and inhibit trophoblast invasion, thereby promoting oxidative stress [69]. Complement system also plays a crucial role in maintaining a healthy pregnancy, and abnormal activation of the complement system would cause maternal systemic inflammatory response, leading to the occurrence of preeclampsia.…”
Section: Immune Dysregulation and Oxidative Stressmentioning
confidence: 99%